CircDTL Functions as an Oncogene and Regulates Both Apoptosis and Ferroptosis in Non-small Cell Lung Cancer Cells - Shanshan, Wang; Hongying, Ma; Jingjing, Fang; Yiming, Yu; Yu, Ren; Rui, Yu (Frontiers in Genetics, 2021)
Background: Circular RNAs (circRNA) play an essential role in the tumorigenesis of non-small cell lung cancer (NSCLC). CircDTL is a novel identified circRNA with little information regarding its biological role. However, the role of circDTL in NSCLC has not been investigated yet. Method: In this study, the levels of circDTL in tissues and cells were measured by RT-PCR. Cell viability was measured by the CCK-8 assay. Cell migration and invasion were evaluated using the wound healing assay and transwell assay, respectively. Cell death was measured by the cell death ELISA kit. The levels of Fe 2+, ROS, MDA and GSH were measured using the commercial kits. The interactions between miR-1287-5p and circDTL/3’UTR GPX4 were verified by dual-luciferase activity assay. The effects of circDTL on tumor growth were evaluated in vivo. Results: CircDTL was found to be upregulated and acted as an oncogene in NSCLC cells. Knockdown of circDTL promoted both apoptosis and ferroptosis of NSCLC cells. It was identified that circDTL exerts its oncogenic effects via the circDTL/miR-1287-5p/GPX4 axis and GPX4 inhibits both ferroptosis and apoptosis. Finally, this study showed that silencing of circDTL promoted the sensitivity of NSCLC cells to chemotherapeutic agents and inhibited the growth of tumors in vivo. Conclusion: CircDTL acts as an oncogene and exerts its effects via the miR-1287-5p/GPX4 axis in NSCLC, providing a potential therapeutic target for NSCLC cancer therapy.